2020
DOI: 10.3390/cells9061362
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Analysis of Circulating Tumor DNA in Localized and Metastatic Prostate Cancer: Evaluation of Clinical Biomarker Potential

Abstract: Novel and minimally-invasive prostate cancer (PCa)-specific biomarkers are needed to improve diagnosis and risk stratification. Here, we investigated the biomarker potential in localized and de novo metastatic PCa (mPCa) of methylated circulating tumor DNA (ctDNA) in plasma. Using the Marmal-aid database and in-house datasets, we identified three top candidates specifically hypermethylated in PCa tissue: DOCK2, HAPLN3, and FBXO30 (specificity/sensitivity: 80%–100%/75–94%). These candidates were further analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…difference between groups was greater than 0.2 (adjusted p-value < 0.05 and |△β| > 0.2) (Bjerre et al, 2020).…”
Section: Differential Analysis Based On Dna Methylation and Gene Expression Profilesmentioning
confidence: 86%
See 1 more Smart Citation
“…difference between groups was greater than 0.2 (adjusted p-value < 0.05 and |△β| > 0.2) (Bjerre et al, 2020).…”
Section: Differential Analysis Based On Dna Methylation and Gene Expression Profilesmentioning
confidence: 86%
“…The CpG sites with more than 50% missing values were excluded, and the remaining missing values were imputed based on K-Nearest Neighbor algorithm ( Wu et al, 2020 ). The CpG sites were identified as statistically significantly different between tumor tissues and matched adjacent normal tissues with adjusted p -value < 0.05, and the absolute value of the mean β value difference between groups was greater than 0.2 (adjusted p -value < 0.05 and |△ β | > 0.2) ( Bjerre et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Plasma from 36 healthy subjects, 61 patients with benign prostatic hyperplasia (BPH), 102 patients with limited prostate cancer and 65 patients with early metastatic PCa (MPCA) were examined, and hypermethylated DOCK2 was detected in the plasma of MPCA patients. It was also found that the levels of DOCK2 methylation also increased positively with increasing tumor volume, revealing that hypermethylated DOCK2 may be an independent predictor of MPCA progression ( Bjerre et al, 2020 ). Furthermore, high levels of DOCK2 hypermethylation were significantly associated with disease recurrence rates after radical prostatectomy ( Bjerre et al, 2019 ).…”
Section: Role Of Dock2 In Diseasesmentioning
confidence: 99%
“…In localized and de novo metastatic prostate cancer, three genes, DOCK2, HAPLN3, and FBXO30, were found to be specifically hypermethylated in prostate cancer tissues using MS-ddPCR [44]. In plasma cfDNA, methylation of these three genes was detected in 61.5% of metastatic prostate cancer patients and was associated with significantly shorter time to progression to metastatic castration-resistant prostate cancer (mCRPC), indicating a potential usefulness for the identification of hormone-na€ ıve metastatic prostate cancer patients who could benefit from intensified treatment [44]. It was also recently reported that DNA methylation in regions of chromosome 8q24 may be associated with the risk of developing prostate cancer [45].…”
Section: Early Detectionmentioning
confidence: 99%